Atomic force microscope with an adjustable probe direction and piezoresistive cantilevers operated in tapping-mode - Schaude, Janik; Albrecht, Julius; Klöpzig, Ute; Gröschl, Andreas Christian; Hausotte, Tino (Technisches Messen, 2019)
This article presents a new tilting atomic forcemicroscope (AFM) with an adjustable probe direction and piezoresistive cantilever operated in tapping-mode.The AFM is based on two rotational axes, which enable the adjustment of the probe direction to cover a complete hemisphere. The whole setup is integrated into a nano measuring machine (NMM-1) and the metrological traceability of the piezoresistive cantilever is warranted by in situ calibration on the NMM-1. To demonstrate the capabilities of the tilting AFM, measurements were conducted on a step height standar
Keywords: Atomic force microscopy; tilting AFM; piezoresistive cantilever; nano measuring machine